Atomic Pt-Layer-Coated Au Peroxidase Nanozymes with Enhanced Activity for Ultrasensitive Colorimetric Immunoassay of Interleukin-12 - Han Zhang; Xiang Peng; Hao Song; Yongfeng Tan; Jianglian Xu; Qunfang Li; Zhuangqiang Gao (Biosensors)
Interleukin-12 (IL-12), a crucial biomarker for immune and inflammatory responses, plays a pivotal role in diagnosing and managing diverse pathological conditions. Although colorimetric enzyme-linked immunosorbent assays (CELISAs) have been extensively employed to detect IL-12 in biological samples, their sensitivity is inherently limited by the catalytic efficiency of enzyme labels, presenting substantial challenges in achieving ultrasensitive detection and enabling pre-symptomatic diagnosis of diseases. In this study, we address this limitation by developing a novel peroxidase nanozyme, featuring ultrathin Pt skins consisting of only ~4 atomic layers, coated on Au nanoparticles (denoted as Au@Pt4LNPs). These Au@Pt4LNPs exhibit remarkable catalytic performance, achieving a ~1063-fold enhancement in peroxidase-like activity compared to horseradish peroxidase (HRP), while minimizing Pt consumption, thereby improving Pt utilization efficiency and reducing costs. This advancement facilitates the construction of an ultrasensitive CELISA capable of detecting IL-12 at femtomolar concentrations. Using Au@Pt4LNPs as the signal labels, the developed CELISA demonstrates a quantitative detection range from 0.1 to 100 pg mL−1, with a limit of detection (LOD) as low as 0.084 pg mL−1 (1.1 fM), offering ~10 times greater sensitivity than the HRP-based CELISA. This study highlights the potential of Au@Pt4LNP nanozymes as advanced signal labels, opening new avenues for next-generation ultrasensitive bioassays.